Morbilidad y contaminación ambiental por la explotación minera en la zona urbana del cantón Zaruma. - Aguilar Ramírez, Diana Nayeli (2024)
ABSTRACT: The main objective of this research study was to estimate the relationship between morbidity and environmental contamination caused by mining in the urban area of Zaruma. For this purpose, a survey was apply to a sample of 370 people as a study group that includes the opinion of the quality of natural resources and their main pollutants. The results showed that most people suffer morbidity as a result of mining; the econometric logit model showed that the factors that influence the probability are the quality of air, soil, biodiversity, gender, education level and income. This last variable is economically associated because, although mining provides monetary benefits, the cost of environmental pollution is producing illnesses in the inhabitants that worsen with the passage of time.